Future horizons for catheter-based interventions in adult congenital and structural heart disease. (March 2012) - Singh, Harsimran S; Osten, Mark; Horlick, Eric
In recent decades, there has been an exponential growth in both the number and range of catheter-based interventions for adult congenital and structural heart disease. In this article, we discuss the rationale for the ongoing development of minimally invasive multidisciplinary interventions; the required training elements necessary to achieve expertise in the field; the cardiac team needed to best perform these interventions; and the currently available and up and coming technologies for performing transcatheter valve therapies.